Automatization and self-maintenance of the O-GlcNAcome catalog: a smart scientific database. (19th July 2021) - Malard, Florian; Wulff-Fuentes, Eugenia; Berendt, Rex R; Didier, Guillaume; Olivier-Van Stichelen, Stephanie
Abstract: Post-translational modifications (PTMs) are ubiquitous and essential for protein function and signaling, motivating the need for sustainable benefit and open models of web databases. Highly conserved O -GlcNAcylation is a case example of one of the most recently discovered PTMs, investigated by a growing community. Historically, details about O -GlcNAcylated proteins and sites were dispersed across literature and in non- O -GlcNAc-focused, rapidly outdated or now defunct web databases. In a first effort to fill the gap, we recently published a human O -GlcNAcome catalog with a basic web interface. Based on the enthusiasm generated by this first resource, we extended our O -GlcNAcome catalog to include data from 42 distinct organisms and released the O -GlcNAc Database v1.2. In this version, more than 14 500 O -GlcNAcylated proteins and 11 000 O -GlcNAcylation sites are referenced from the curation of 2200 publications. In this article, we also present the extensive features of the O -GlcNAc Database, including the user-friendly interface, back-end and client–server interactions. We particularly emphasized our workflow, involving a mostly automatized and self-maintained database, including machine learning approaches for text mining. We hope that this software model will be useful beyond the O -GlcNAc community, to set up new smart, scientific online databases, in a short period of time. Indeed, this database system can be administrated with little to no programming skills and is meant to be an example of a useful, sustainable and cost-efficient resource, which exclusively relies on free open-source software elements (www.oglcnac.mcw.edu ).